Strategi Badan Narkotika Nasional (BNN) Kota Denpasar dalam Pencegahan Penyalahgunaan dan Peredaran Narkoba - Widhi Antari, Ni Putu Bayu (Jurnal Ilmiah Widya Sosiopolitika; Vol 5 No 2 (2023): DIPLOMASI DAN ISU-ISU INTERNASIONAL, 2023)
This study aims to describe the strategy of the Denpasar City National Narcotics Agency in preventing drug abuse and distribution. The researcher used a qualitative method with a descriptive approach through data sources obtained from observation, interviews and documentation with the research informants being the Denpasar City National Narcotics Agency and the community. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The technique of checking the validity of the data uses triangulation, namely source triangulation and method triangulation. The results of this study found that the Denpasar City National Narcotics Agency in preventing drug abuse and distribution has been carried out comprehensively by implementing the most basic strategic programs in prevention, eradication, abuse and illicit drug trafficking such as promotive, preventive, curative, rehabilitation and repressive programs. In implementing the prevention strategy mentioned above, the Denpasar national narcotics agency applies four strategies, namely soft power strategy (prevention efforts, community empowerment and rehabilitation), hard power (efforts to eradicate crime), smart power (utilization of information technology and social media), and cooperation